Recruited Exudative Macrophages Selectively Produce CXCL10 after Noninfectious Lung Injury - Tighe, Robert M. (American Thoracic Society, 2011)
The chemokine, CXCL10, and its cognate receptor, CXCR3, are important mediators of the pathobiology of lung fibrosis. Macrophages are a known source of CXCL10, but their specific source in the lung is poorly defined due to incomplete characterization of macrophage subpopulations. We recently developed a novel flow cytometric approach that discriminates resident alveolar macrophages from recruited exudative macrophages (ExMacs) after infectious lung injury. We hypothesized that ExMacs are present after noninfectious lung injury with bleomycin, and are a source of CXCL10. We found that ExMacs are recruited to the lung after injury, peaking at Day 7, then maintained through Day 28. ExMac recruitment was significantly reduced, but not abolished, in CCR2 null mice. ExMacs, but not alveolar macrophages, produce CXCL10, both constitutively and after stimulation with hyaluronan (HA) fragments. Interestingly, ExMac stimulation with LPS resulted in complete suppression of CXCL10. In contrast, ExMacs produced TNF-α and CXCL2/MIP-2 (Macrophage Inflammatory Protein-2) after stimulation with both HA and LPS. ExMacs were present in CXCR3 null mice after bleomycin, but produced minimal CXCL10. This impairment was overcome by administration of exogenous IFN-γ or IFN-γ with HA. Collectively, these data suggest that ExMacs are recruited and maintained in the lung after noninfectious lung injury, are a source of a variety of cytokines, but importantly, are essential for the production of antifibrotic CXCL10. Understanding the contribution of ExMacs to the pathobiology of lung injury and repair could lead to new treatment options for fibrosing lung diseases.